Analisis Validitas dan Reliabilitas Alat Peraga Tabung Resonansi Horizontal beserta Instrumennya untuk Menunjang Keterampilan Generik Sains Siswa - Choirul Huda; Feny Febriana Damayanti; Duwi Nuvitalia (Physics Education Research Journal, 2019)
The purpose of this research to determine the validity and reliability of instrument and horizontal resonance tubes props to support student’s generic science skills. The instrument used in this research is the observation sheet with the number of 10 student activities observed. The learning media used are products in the form of horizontal resonance tube props and props usage guidelines. This research is a qualitative descriptive study to assess and determine the quality of instrument and props to support student’s generic science skills. Each instrument and props were validated by two physics education experts. The results showed: 1) the average validation results by the two experts were in very valid criteria with a percentage of 85.42% for observation sheets, 91.67% for horizontal resonance tube props, and 100% for usage guidelines tool; 2) product reliability is on the reliable criteria with the percentage of observation sheet instruments 88.23%, horizontal resonance tube props 97.06%, and guidelines for using the tools 100%. Based on the results of the research, instruments and horizontal resonance are proper to be used to support students' generic science skills with very valid and reliable criteria.